(untitled) (Baghdad Science Journal, 2025)
As a marker of systemic inflammation, raised (C-reactive protein (CRP)) concentrations which are still within the normal range have been associated with an increased inflammation of chronic renal diseases (CRD). The current study aimed to establish potential determinats of raised CRP concentrations in patients who treated in Heamodialysis room,then study the relationship between CRP& some biochemical parameters related CRD We used a CRP latex reagents Kit which is based on an immunological reaction between CRP antisera bounded to the biologically inert latex particles or with CRP in the test specimens of 19 patients with (CRD) mean age 48 years ,range = 30?65 & in 21 healthy subjects as control group their age range = 30 ?45 years. The results are classified according to visible agglutination to: 1-A positive result / is indicated by the obvious agglutination pattern of the latex, in a clear solution. 2-A negative result / is indicated by no change in the latex suspension on the test slide. Then, we correlated the results of the precipitin test with the quantitative data on C-reactive protein. This study has found that: CRP concentrations in patients with CRD were increased very clearly than normal subjects , and established that CRP concentration in male was more than in female for patients specimens. Biochemical studies have shown raising (CRP) concentration is a marker of systemic inflammation. The relation between CRP & S.creatinine ,hemoglobine ,blood sugar is negative ,while positive with blood urea . Other biochemical parameter related to CRD’’ blood urea, blood creatinine & hemoglobine and blood sugar’’ were assayed for both subjects in order to asses the disease by compared the results. Abbreviation: CRP:C-reactive protein, CRD: Chronic renal diseases, F: Female, M: Male, Hb: hemoglobin, BU: blood Urea, S.Cr: Serum creatinine, BS: blood sugar, nCRP: native CRP, MCRP: Matified CRP.